2015
DOI: 10.15252/emmm.201404318
|View full text |Cite
|
Sign up to set email alerts
|

Defects in mitophagy promote redox‐driven metabolic syndrome in the absence of TP 53 INP 1

Abstract: The metabolic syndrome covers metabolic abnormalities including obesity and type 2 diabetes (T2D). T2D is characterized by insulin resistance resulting from both environmental and genetic factors. A genome-wide association study (GWAS) published in 2010 identified TP53INP1 as a new T2D susceptibility locus, but a pathological mechanism was not identified. In this work, we show that mice lacking TP53INP1 are prone to redox-driven obesity and insulin resistance. Furthermore, we demonstrate that the reactive oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 56 publications
4
42
0
Order By: Relevance
“…This redox role is also important for the control of lipid metabolism, both in vitro (TP53INP1-deficient cells accumulate lipid droplets) and in vivo (fat mass is aberrantly abundant in TP53INP1-deficient mice). Altogether, these observations reveal a mechanism for the genome-wide association study (GWAS)-identified role of TP53INP1 in Type 2 Diabetes promoted by obesity [67]: TP53INP1 participation in mitophagy prevents the accumulation of mitochondria producing ROS which favor lipid accumulation [21].…”
Section: Tp53inp1 Is Involved In Metabolic Homeostasis Through Autophagymentioning
confidence: 91%
See 4 more Smart Citations
“…This redox role is also important for the control of lipid metabolism, both in vitro (TP53INP1-deficient cells accumulate lipid droplets) and in vivo (fat mass is aberrantly abundant in TP53INP1-deficient mice). Altogether, these observations reveal a mechanism for the genome-wide association study (GWAS)-identified role of TP53INP1 in Type 2 Diabetes promoted by obesity [67]: TP53INP1 participation in mitophagy prevents the accumulation of mitochondria producing ROS which favor lipid accumulation [21].…”
Section: Tp53inp1 Is Involved In Metabolic Homeostasis Through Autophagymentioning
confidence: 91%
“…Nuclear localization is also observed upon oxidative stress through redox-driven sumoylation [20]. In other contexts, TP53INP1 is found in the cytoplasm, in autophagosomes during autophagy, as well as in mitochondria [17,21]. The mechanism responsible for addressing TP53INP1 to these different cellular compartments remains to be elucidated.…”
Section: Identification Of Tp53inp1mentioning
confidence: 99%
See 3 more Smart Citations